How Does the Learning of Paradox Influence Individuals' Capacity to Navigate Wicked Problems? - Hameed, Raja Mazhar; Ullah, Irfan; Abbas, Farrukh (Journal of Social Sciences & Humanities (1994-7046))
This research explores how the learning paradox influences individuals' capacity to navigate wicked problems. Adopting a phenomenological approach, the study aims to investigate the experiences of individuals who have encountered and successfully tackled wicked problems in their personal and professional lives. The study employed a qualitative research design, utilizing interviews as the primary data collection method. A thematic analysis approach was employed to analyze the interview data and uncover key themes and patterns related to the learning of paradox. The purpose of this study was to examine how individuals perceive and make sense of paradoxical situations and how this learning impacts their ability to effectively address and navigate complex, wicked problems. The findings reveal that individuals who embrace paradoxical thinking are better equipped to navigate wicked problems, demonstrating cognitive flexibility by holding contradictory ideas in their minds simultaneously. This ability enables them to explore diverse perspectives, embrace complexity, and transcend binary thinking to generate innovative solutions. Additionally, the study highlights that individuals who navigate paradoxes effectively possess the capacity to adapt to evolving circumstances and problem contexts. Wicked problems often exhibit dynamic and unpredictable features, demanding agile responses. Those who can comfortably engage with paradoxes demonstrate an enhanced ability to shift perspectives, reframe problems, and adjust strategies in response to emerging information and evolving circumstances. This adaptability enables individuals to remain resilient and responsive in the face of uncertainty and complexity. The implications of these findings extend to education and training programs, where educators and trainers can harness the power of paradoxical learning to enhance problem-solving and decision-making skills. By incorporating activities that encourage the exploration of paradoxes, educators can cultivate cognitive flexibility and promote creative problem-solving among learners. Real-world case studies of wicked problems provide valuable opportunities for learners to grapple with complexity, engage in divergent thinking, and develop the ability to hold conflicting ideas in tension.